Role of Subjective Well-Being in Intercultural Adaptation - E Ju Chebotareva (RUDN Journal of Psychology and Pedagogics, 2014)
The article presents the study of subjective well-being correlations with such factors of intercultural communication, as ethnic identity, communicative tolerance, as well as some personality traits. Subjective well-being is positively related to ethnic identity and, ambiguously, to communicative tolerance. The main positive role in the intercultural communication is played by a person's satisfaction with the social support received, which is inversely related to some forms of extremist manifestations of ethnic identity and with many manifestations of intolerance. In contrast, satisfaction with daily activities, good self-reported health and mood stability are directly related to some forms of intolerance.